PENGARUH LITERASI DIGITAL TERHADAP KOMPETENSI PEDAGOGIK MAHASISWA CALON GURU: PERAN SELF-EFFICACY SEBAGAI VARIABEL MEDIASI - Butar-Butar, Agustina; Manek, Alfridus Mau (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Pedagogical competence is one of the main competencies that prospective teacher students must have to support successful learning in the digital era. However, based on observations of students in the Economics Education Study Program, Faculty of Teacher Training and Education, Nusa Cendana University, limitations are still found in learning planning, technology utilization, and student-centered learning implementation. This study aims to analyze the influence of digital literacy on the pedagogical competence of prospective teacher students, the influence of digital literacy on self-efficacy, the influence of self-efficacy on pedagogical competence, and the role of self-efficacy as a mediating variable. The study used a quantitative approach with an explanatory research type. The study population was 233 students, with a sample of 105 students selected using a voluntary sampling technique. Data were collected through questionnaires and analyzed using PLS-SEM with the help of SmartPLS 4. The results showed that digital literacy had a positive and significant effect on pedagogical competence (β = 0.396; p < 0.001) and self-efficacy (β = 0.803; p < 0.001). Self-efficacy also had a positive and significant effect on pedagogical competence (β = 0.547; p < 0.001). Furthermore, self-efficacy was shown to positively and significantly mediate the effect of digital literacy on pedagogical competence (β = 0.439; p < 0.001). This study concluded that improving digital literacy can improve the pedagogical competence of student teachers directly and through strengthening self-efficacy.